Análise do modelo troposférico empregado na geração de uma estação de referência virtual utilizando o posicionamento por ponto preciso - Marra Alves, Daniele Barroca [UNESP]; Galera Monico, Joao Francisco [UNESP]; Antonio Dalbelo, Luiz Fernando [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2009)
In the past few years the interest is accomplishing a high accuracy positioning increasing. One of the methods that has been applied by the scientific community is the network based on positioning. By using multiple reference station data, it is possible to obtain centimetric positioning in a larger coverage area, in addition to gain in reliability, availability and integrity of the service. Besides, using this concept, it is possible to model the atmospheric effects (troposphere refraction and ionosphere effect). Another important question concerning this topic is related to the transmission of the network corrections to the users. There are some possibilities for this fact and an efficient one is the Virtual Reference Station (VRS) concept. In the VRS concept, a reference station is generated near to the rover receiver (user). This provides a short baseline and the user has the possibility of using a single frequency receiver to accomplish the relative positioning. In order to test this kind of positioning method, a software has been developed at São Paulo State University. In this paper, the methodology applied to generate the VRS data is described and the VRS quality is analyzed by using the Precise Point Positioning (PPP) method.
Analysing of a tropospheric model so as to generated a virtual reference station by using a precise point positioning method
Keywords: Network Based Positioning; VRS; Tropospheric Model